2020
DOI: 10.3389/fncel.2020.606142
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Vesicles Dynamics in Neocortical Epilepsy

Abstract: Neuronal hyperexcitability often results from an unbalance between excitatory and inhibitory neurotransmission, but the synaptic alterations leading to enhanced seizure propensity are only partly understood. Taking advantage of a mouse model of neocortical epilepsy, we used a combination of photoconversion and electron microscopy to assess changes in synaptic vesicles pools in vivo. Our analyses reveal that epileptic networks show an early onset lengthening of active zones at inhibitory synapses, together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…Affecting ~50 million people worldwide, epilepsy is a central nervous system disorder with spontaneous seizures as the main symptom (Li et al, 2015 ; Vannini et al, 2020 ). In lesional epilepsy, seizures develop in response to brain damage (Pitkänen and Immonen, 2014 ), while in non-lesional epilepsy they are the result of altered synaptic function (Farisello et al, 2013 ; Vannini et al, 2020 ). These seizures are caused by high frequency, synchronous and uncontrolled synaptic transmission in the brain (Li et al, 2015 ; Vannini et al, 2020 ).…”
Section: Neurological Diseases Related To Svrmentioning
confidence: 99%
See 2 more Smart Citations
“…Affecting ~50 million people worldwide, epilepsy is a central nervous system disorder with spontaneous seizures as the main symptom (Li et al, 2015 ; Vannini et al, 2020 ). In lesional epilepsy, seizures develop in response to brain damage (Pitkänen and Immonen, 2014 ), while in non-lesional epilepsy they are the result of altered synaptic function (Farisello et al, 2013 ; Vannini et al, 2020 ). These seizures are caused by high frequency, synchronous and uncontrolled synaptic transmission in the brain (Li et al, 2015 ; Vannini et al, 2020 ).…”
Section: Neurological Diseases Related To Svrmentioning
confidence: 99%
“…In lesional epilepsy, seizures develop in response to brain damage (Pitkänen and Immonen, 2014 ), while in non-lesional epilepsy they are the result of altered synaptic function (Farisello et al, 2013 ; Vannini et al, 2020 ). These seizures are caused by high frequency, synchronous and uncontrolled synaptic transmission in the brain (Li et al, 2015 ; Vannini et al, 2020 ). SVR plays a clear role in this abnormal synaptic transmission by maintaining the neurotransmission of the central synapses (Li et al, 2015 ).…”
Section: Neurological Diseases Related To Svrmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, another recent study found altered synaptic vesicle dynamics that were inhibitory or excitatory synapse-specific in the tetanus toxin epilepsy mouse model. 10 This, combined with the increasing number of genetic variants that cause epilepsy found in synaptic vesicle associated proteins (e.g., DNM1 , STXBP1 , and SNAP25 ) makes it clear that the relevance of presynaptic vesicle dynamics to seizure occurrence is a topic worthy of further inquiry.…”
Section: Commentarymentioning
confidence: 99%
“…Neurotransmitters and neuroendocrine axes are critical in the onset of epilepsy ( Camfield et al, 2017 ). Although the molecular mechanism of epilepsy has not been fully elucidated, there is growing evidence for synaptic transmission in the pathological process of epilepsy ( Amador et al, 2020 ; Puhahn-Schmeiser et al, 2021 ), and altered dynamics of inhibitory synapses and excitatory synapses may be a critical signature of epileptic networks ( Vannini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%